Resolution or Interest Oriented Policy? International Influence on the Cyprus Conflict Between 1960-1974 - Yakup Kaya; Merve Gönlühoş Elmas (Yakın Dönem Türkiye Araştırmaları)
When discussing the geopolitical dynamics of the Eastern Mediterranean, Cyprus consistently emerges as one of the prominent islands in the region. Hence, the island has experienced a significant degree of international influence. The influence primarily stems from discourses surrounding peace and security, yet this study contends that the actuality diverges from this perspective. Basically, the argument posited in this article asserts that the involvement of foreign actors in the affairs of other states does not lead to the establishment of lasting peace or security. The era between 1960 and 1974 stands out as a particularly supportive timeframe for this assertion. This study aims to present the narratives of key international and regional actors during the Cyprus Crisis, thereby documenting this specific historical era. In this context, Greece and the UK are particularly noteworthy whereas Türkiye with its common history plays the most important role in keeping peace in accordance with the international law. Thus, the primary objective of this study is to uncover the underlying reality or reason behind the discourses through the implementation of a case analysis. In fact, the main idea presented in the study suggests that the prompt achievement of peace and security could be facilitated without the involvement of international actors without any ties to the region. The study provides insight into the objectives of international actors and the potential challenges faced by Cyprus.In the article, Turkish, British and American archive documents, Turkish and British newspapers, as well as domestic and foreign copyrighted works on the subject were used.